A retrospective analysis of clinical characteristics and management of perianal streptococcal dermatitis in children and adults - Šterbenc, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2021)
Introduction: Due to the paucity of recent literature on perianal streptococcal disease (PSD), we performed a comprehensive analysis of clinical characteristics of PSD and its management. Methods: We conducted a retrospective search in the laboratory information system of the Institute of Microbiology and Immunology, Ljubljana, Slovenia, between January 2006 and December 2016 and identified patients with suspected PSD. We reviewed patients' medical records and obtained data on patient age and sex, concomitant illnesses, duration of complaints, signs and symptoms of PSD, epidemiological history, date of diagnosis, microbiological characteristics of beta-hemolytic streptococcal isolates, additional laboratory findings, duration and type of systemic and/or topical therapy, and recurrence of PSD. Results: We identified 64 pediatric and eight adult PSD cases in total. The most common signs and symptoms were perianal erythema (67/72; 93.1%), anal fissures (28/72; 38.8%), itching (22/72; 30.6%), and blood-streaked stools (19/72; 26.4%). The duration of symptoms varied from 1 year, with 58.3% of patients experiencing symptoms between 1 week and 6 months. The majority of patients received systemic (63/72; 87.5%) and topical (56/72; 77.8%) treatment. Conclusions: Although the signs and symptoms of PSD are non-specific, clinicians should be highly suspicious of the disease in adults and especially in preschool children with perianal complaints. Despite being a common disease, there is still considerable delay in correct diagnosis and treatment, prolonging the discomfort of PSD patients.
Keywords: analiza; analysis; clinical characteristics; dermatitis; klinične značilnosti; perianal streptococcal disease; perianalni dermatitis; streptokoki